2017
DOI: 10.1038/srep40723
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB suppresses apoptosis and promotes bladder cancer cell proliferation by upregulating survivin expression in vitro and in vivo

Abstract: Nuclear factor kappa-B (NF-κB) activation is a common phenomenon in cancers, which results in the aberrant expression of NF-κB target genes and leads to malignant transformation, metastatic dissemination, abnormal cell proliferation or resistance to cell death. Survivin is a unique member of the IAP family, a well-known cancer-specific molecule and a molecular marker of poor clinical outcome in several cancer types, including bladder cancer. YM-155, a potent survivin suppressor, has been shown to have anti-tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 49 publications
1
62
1
Order By: Relevance
“…Constitutive NF‐κB activation was observed in high grade bladder cancer . Many studies indicated inhibition of NF‐κB activation suppresses tumor growth, anti‐apoptosis, angiogenesis, and metastatic potential in bladder cancer in vitro and in vivo . In our results demonstrated NF‐κB activation and expression of tumor progression‐associated proteins were significantly decreased by QNZ (NF‐κB inhibitor) in TSGH‐8301 cells.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Constitutive NF‐κB activation was observed in high grade bladder cancer . Many studies indicated inhibition of NF‐κB activation suppresses tumor growth, anti‐apoptosis, angiogenesis, and metastatic potential in bladder cancer in vitro and in vivo . In our results demonstrated NF‐κB activation and expression of tumor progression‐associated proteins were significantly decreased by QNZ (NF‐κB inhibitor) in TSGH‐8301 cells.…”
Section: Discussionsupporting
confidence: 56%
“…31 Many studies indicated inhibition of NF-κB activation suppresses tumor growth, anti-apoptosis, angiogenesis, and metastatic potential in bladder cancer in vitro and in vivo. 32,33 In our results 34 NF-κB activation may be regulated by AKT or MAPKs cascades. 11 We used NF-κB reporter gene assay to evaluate effect of AKT or MAPK inhibitors on NF-κB activation in TSGH 8301 cells.…”
Section: Discussionmentioning
confidence: 58%
“…Cell lines of human BC, T24 and 5637, were obtained from the Typical Culture Preservation Commission Cell Bank of the Chinese Academy of Sciences (Shanghai, China). Cell lines were cultured in RPMI-1640 medium supplemented with 1% penicillin/streptomycin and 10% FBS (all from HyClone; GE Healthcare Life Sciences, Logan, UT, USA) and under a humidified atmosphere of 5% CO 2 at 37˚C (15).…”
Section: Methodsmentioning
confidence: 99%
“…BCa is manifested with highly recurrent multiple tumors [22,23]. Clinical tumor staging, pathological grade, and lymph node metastasis have been proven to be vital predictors of clinical prognosis [24]. Numerous studies have demonstrated that pathological grading and clinical tumor staging play pivotal roles are associated with lymph node metastasis and predict clinical prognosis of patients with BCa in clinical practice.…”
Section: Discussionmentioning
confidence: 99%